SHAPING YOUTH ATTITUDES TOWARDS PEOPLE WITH PHYSICAL DISABILITIES – RESEARCH REPORT - Magdalena Wędzińska (Különleges Bánásmód, 2020)
The objective of this article is to present the results of studies on attitudes of secondary school students towards people with physical disabilities. The research was conducted among pupils of high schools, technicians, and professional schools in Poland. On the basis of the results of the research, it can be stated that the attitudes of young people towards people with physical disabilities vary (from negative to very positive). Moreover, attitudes towards people with physical disabilities are related to knowledge about physical disability and perception of parents' attitudes towards people with physical disabilities.